Pengembangan SDM Tenaga Pendidik di Madrasah Aliyah Nurul Islam Ngemplak Boyolali Menghadapi Abad ke-21 - Mujiburrohman; Daliman; Haidar Amru; Shofiyurrohman Al M (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article discusses the development of human resources (HR) of educators at Madrasah Aliyah Nurul Islam Ngemplak Boyolali in facing the challenges of the 21st century. This research was conducted with the aim of analyzing the strategies and approaches applied in developing the human resources of teaching staff and their impact on the implementation of education in the madrasah. The research method used was a qualitative case study, involving data collection through interviews, observation, and document analysis. The results showed that Madrasah Aliyah Nurul Islam Ngemplak Boyolali implemented various efforts to develop educators' human resources, including continuous training, developing pedagogical competence, and utilizing educational technology. The development of educators' human resources has had a positive impact on the quality of the learning process and student achievement. However, challenges such as curriculum changes, technological developments, and increasingly complex demands of society are also faced. In the 21st century, this article recommends the need for increased cooperation among madrasahs, the government, and various related parties to support the development of educators' human resources. In addition, the implementation of sustainable strategies in developing pedagogical competencies and adapting to the development of educational technology is key to changing times. Thus, Madrasah Aliyah Nurul Islam Ngemplak Boyolali can continue to grow and make a significant contribution to preparing a generation that is ready to face future challenges.